Mulheres negras: projetos de vida - Ramos, Juliana de Souza (2015)
The core of this research was to show that the development of resilience among three generations of black women is culturally invested. The periodized life turns out to establish relationships between groups of different age, articulating an important dimension to understand the forms of resistance, formation of self-esteem, family and ethnic sense of belonging. As a methodology, were conducted interviews, questionnaires and participant observation about the different generations of black women (in this case Grandparents, mothers and daughters) living in the city of Diadema. As a result of the analysis and, in addition to in depth knowledge of the issues involving generations, black advocacy, public policies (especially in education), family and memories, the research indicated that families go through a process of reinvention in which feminine generations assume their role as protagonists of their lives. They are the majority in the formal and informal labor market, articulating the decline in fertility. They are also the ones that have the highest life expectancy rate (even with double and/or triple shift of work) and that, when it comes to education, are outperforming black men. And, doing so, they are changing the black feminine universe, once remembered mainly by lower wages and grades of schooling when compared to other Brazilians